Effleurage Massage and Deep Back Massage’s Different Effects on Menstrual Pain - Yuliyanti, Irma Dwi; Ariyanti, Lilik; Amarseto, Binuko (Indonesian Journal of Global Health Research, 2024)
Menstrual pain is one of the illnesses that arise throughout the menstrual cycle and can interfere with daily activities. Lower abdominal pain brought on by menstruation is known as menstrual pain. Menstrual pain can be treated with both pharmaceutical and non-pharmacological methods. Massage is a non-pharmacological treatment. determine the difference in the effect between effleurage massage and deep back massage on reducing menstrual pain. This study's design was pre-experimental, with no control group and two pre-test-post-test intervention groups. There were 22 teens in the population, ages 20 to 24. The Numerical Rating Scale is used to measure pain (NRS). For two months, the study used dosages twice a month. According to research, 30% of participants in the deep back massage intervention group and 100% of participants in the effleurage massage intervention group reported having severe discomfort. Following the intervention, the deep back massage group experienced a 10% reduction in discomfort, whereas the effleurage massage group experienced a 70% drop. This means that deep back massage and effleurage massage are thought to be beneficial in lowering menstruation pain, as shown by a p value of 0.000 < 0.005. P value for the Mann Whitney test is 0.067. There is no difference between effleurage massage and deep back massage in reducing pain levels in women with menstrual pain. Effleurage massage and deep back massage work similarly in terms of lowering pain thresholds in women who are having menstruation pain.